2013
DOI: 10.1016/j.biortech.2013.01.158
|View full text |Cite
|
Sign up to set email alerts
|

Biomass torrefaction: Modeling of reaction thermochemistry

Abstract: ABSTRACT:Based on the evolution of volatile and solid products predicted by a previous model for torrefaction (Bates and Ghoniem, 2012) a model has been developed which describes their thermal, chemical, and physical properties as well as the rates of heat release. The first stage of torrefaction, associated with hemicellulose decomposition, is exothermic releasing between 40-280 kJ/kg initial . The second stage is associated with the decomposition of the remaining lignocellulosic components, completes over a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
47
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(50 citation statements)
references
References 25 publications
3
47
0
Order By: Relevance
“…It was a challenge to find values for h r as the torrefied material was not well defined, it comprises fibers (mostly cellulose) and a large variety of plastic materials. Cellulose torrefaction in the 25-300 • C temperature range starts as an endothermic reaction and continues as an exothermic reaction (Bates and Ghoniem, 2013). Enthalpies of reaction for plastic in the same temperature range were always positive and vary in the range (12.55-147.86 J/kg) (Zhao et al, 2017), which is smaller than the value of c p (T-T o ) (∼400 kJ/kg) in Equation (4).…”
Section: Torrefactionmentioning
confidence: 75%
“…It was a challenge to find values for h r as the torrefied material was not well defined, it comprises fibers (mostly cellulose) and a large variety of plastic materials. Cellulose torrefaction in the 25-300 • C temperature range starts as an endothermic reaction and continues as an exothermic reaction (Bates and Ghoniem, 2013). Enthalpies of reaction for plastic in the same temperature range were always positive and vary in the range (12.55-147.86 J/kg) (Zhao et al, 2017), which is smaller than the value of c p (T-T o ) (∼400 kJ/kg) in Equation (4).…”
Section: Torrefactionmentioning
confidence: 75%
“…Longer residence time releases more volatiles gases and leads to the evolution of a secondary volatiles gases, which has relatively a higher energy value than the first stage volatiles. For instance, Bates and Ghoniem (2013) found that the first stage volatile in the two-step torrefaction kinetics has heating the value of only 4.4 MJ/kg compared to 16 MJ/kg in the second stage volatiles. The carbon usually contributes 60-85% of the total mass of the coal composition, whereas the oxygen content ranges from 5-20% (Prins et al, 2007).…”
Section: Proximate and Ultimate Analysismentioning
confidence: 99%
“…The advantage of this kinetic mechanism and set of parameters is that all pseudo-components (A,B,C,V1,V2) have welldefined chemical compositions thus enabling estimation of their thermodynamic properties, namely their heat of formation and specific heat capacity [58]. Thus, the elemental balance enables the estimation of the solid product composition and energy yield [59] not considered in previous single particle models.…”
Section: V1 V2mentioning
confidence: 99%
“…Thermodynamic properties of the solid phases (A,B,C,S) and V1 and V2 are summarized in Table 2. For further information on the thermodynamic property estimation of the solid and volatile products see [58]. The effective conductivity of the solid matrix described in Table 2 includes a contribution from radiation heat transfer through the pore spaces [12] as wells as a contribution from the moisture [43,48].…”
Section: Conservation Of Energymentioning
confidence: 99%
See 1 more Smart Citation